Cloning and characterization of a Pseudomonas aeruginosa gene involved in the negative regulation of phosphate taxis. - Kato, J (1994)
Pseudomonas aeruginosa PAO1 exhibited a positive chemotactic response to P(i). The chemotactic response was induced by P(i) limitation. An alkaline phosphatase (AP) constitutive mutant showed a chemotactic response to P(i), regardless of whether the cells were starved for P(i). Sequence analysis and complementation studies showed that the P. aeruginosa phoU gene was involved both in the regulation of AP expression and in the induction of P(i) taxis. However, unlike AP expression, P(i) taxis was not regulated by the phoB gene product.